How to deal with atrial septal defect closure from right internal jugular vein: Role of venous‐arterial circuit for sizing and over‐the‐wire device implantation. Issue 1 (17th June 2016) - Butera, Gianfranco; Lovin, Nicusor; Basile, Domenica Paola
Abstract : Secundum atrial septum defect (ASD) is the most common congenital heart disease. It is usually treated by a transcatheter approach using a femoral venous access. In case of bilateral femoral vein occlusion, the internal jugular venous approach for ASD closure is an option, in particular in cases where ASD balloon occlusion test and sizing is needed. Here, we report on a new technique for ASD closure using a venous‐arterial circuit from the right internal jugular vein to the femoral artery. Two patients (females, 4 and 10 years of age) had occlusion of both femoral veins because of a previous history of pulmonary atresia and intact ventricular septum, for which they underwent percutaneous radiofrequency perforation and balloon angioplasty. These subjects needed balloon occlusion test of a residual ASD to size the hole and to check for hemodynamic suitability to ASD closure. After performing a venous‐arterial circuit, a 24 mm St Jude ASD sizing balloon catheter was advanced over the circuit and the defect closed for 15 min to check hemodynamics and size the defect. ASD was closed is hemodinamically suitable. This technique was safe and reliable. © 2016 Wiley Periodicals, Inc.